Isolation and characterisation of 13 pterosins and pterosides from bracken (Pteridium aquilinum (L.) Kuhn) rhizome. (August 2016) - Mohammad, Rizgar Hassan; Nur-e-Alam, Mohammad; Lahmann, Martina; Parveen, Ifat; Tizzard, Graham J.; Coles, Simon J.; Fowler, Mark; Drake, Alex F.; Heyes, Derren; Thoss, Vera
Abstract: Systematic phytochemical investigations of the underground rhizome of Pteridium aquilinum (L.) Kuhn (Dennstaedtiaceae) afforded thirty-five pterosins and pterosides. By detailed analysis of one- and two-dimensional nuclear magnetic resonance spectroscopy, circular dichroism (CD) and high-resolution mass spectrometric data, thirteen previously undescribed pterosins and pterosides have been identified. Interestingly, for the first time 12- O - β -D-glucopyranoside substituted pterosins, rhedynosides C and D, and the sulfate-containing pterosin, rhedynosin H, alongside the two known compounds, histiopterosin A and (2 S )-pteroside A2, were isolated from the rhizomes of subsp. aquilinum of bracken. In addition, six-membered cyclic ether pterosins and pterosides, rhedynosin A and rhedynoside A, are the first examples of this type of pterosin-sesquiterpenoid. Additionally, the three previously reported compounds (rhedynosin I, (2 S )-2-hydroxymethylpterosin E and (2 S )-12-hydroxypterosin A) were obtained for the first time from plants as opposed to mammalian metabolic products. Single crystal X-ray diffraction analysis was applied to the previously undescribed compounds (2 R )-rhedynoside B, (2 R )-pteroside B and (2 S )-pteroside K, yielding the first crystal structures for pterosides, and three known pterosins, (2 S )-pterosin A, trans -pterosin C and cis -pterosin C. Rhedynosin C is the only example of the cyclic lactone pterosins with a keto group at position C-14. Six selected pterosins ((2 S )-pterosin A, (2 R )-pterosin B and trans -pterosin C) and associated glycosides ((2 S )-pteroside A, (2 R )-pteroside B and pteroside Z) were assessed for their anti-diabetic activity using an intestinal glucose uptake assay; all were found to be inactive at 300 μM. Graphical abstract: Thirteen previously undescribed pterosins and pterosides were isolated from bracken rhizomes in north of Wales. Their structures were elucidated using NMR spectroscopic and high resolution FT-ICR-MS data. Highlights: 35 pterosins, 13 previously undescribed compounds in British bracken rhizomes. Single crystal X-ray obtained for 3 pterosins and 3 pterosides. Anti-diabetic activity of pterosins was not observed at concentration 300 μM. Diverse structural features previously unreported for pterosins and pterosides.